ANDROID-BASED UTILITY FACILITY MAINTENANCE APPLICATION USING DYNAMIC SYSTEM DEVELOPMENT METHODOLOGY (DSDM) - Edison Siregar, Master; Mayatopani, Hendra; Kurniawan, Rido Dwi; Prathama, Dhion Angga (Jurnal Teknik Informatika (Jutif), 2024)
In the ever-evolving digital era, the maintenance of utility facilities is becoming increasingly important to ensure smooth operations and services. Utility facilities include critical infrastructure such as waterways, electricity, and communication networks that must be properly maintained to maintain their function and reliability. The main contribution of this research is the application of DSDM in the development of related applications to improve the maintenance efficiency of utility facilities. organizational challenges faced in managing maintenance processes effectively, including untimely reporting issues, poor coordination, and lack of integration with company systems. To address this issue, this paper presents the development of an Android-based application designed to streamline and improve the maintenance process of utility facilities. The application leverages the Dynamic Systems Development Methodology (DSDM), known for its iterative and incremental approach, to ensure on-time delivery and adaptability to changing needs. The main goal of the app is to provide facility managers and maintenance personnel with a comprehensive solution through features such as real-time reporting, maintenance scheduling, and task management. By implementing DSDM in the context of utility maintenance, application users can be actively involved in the entire development process, allowing for rapid adaptation to changing needs The results of the development of this application are expected to improve the maintenance management of utility facilities efficiently, encourage preventive maintenance, and optimize the performance of these vital infrastructures.